2004
DOI: 10.5194/hess-8-327-2004
|View full text |Cite
|
Sign up to set email alerts
|

Measuring rainfall to a forest canopy: an assessment of the performance of canopy level raingauges

Abstract: Accurate rainfall measurements are crucial for water resource and environmental assessments but can be difficult to achieve in extensive areas of forest. This paper reviews the different techniques for measuring rainfall to a forest area and presents the results of a 5-year experiment comparing the catches of gauges installed above a forest canopy with those of ground level gauges outside the forest. It examines the consistency of the catches between the canopy gauges, the sensitivity of the catch to the heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Spatial rainfall patterns are not affected by this adjustment, since the network rain gauges are identical. Robinson et al [2004] found that gauges installed at or just above canopy height agree well with those in nearby gauges outside the forest, but they cited one study for which rain totals abruptly drop to 80% of nominal values when the gauge was greater than 4 m above the canopy. We have insufficient detailed information about the sensor type and exposure to understand the large difference between the km67 and Casa da Onça rainfall totals.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial rainfall patterns are not affected by this adjustment, since the network rain gauges are identical. Robinson et al [2004] found that gauges installed at or just above canopy height agree well with those in nearby gauges outside the forest, but they cited one study for which rain totals abruptly drop to 80% of nominal values when the gauge was greater than 4 m above the canopy. We have insufficient detailed information about the sensor type and exposure to understand the large difference between the km67 and Casa da Onça rainfall totals.…”
Section: Discussionmentioning
confidence: 99%
“…Current weather observations are exposed to biases due to: (1) human perception (e.g. Kent and Berry, 2004), (2) methods for measuring based on "surrogate" variables (e.g., spectral radiance, radar reflectivity, turbulence used to measure cloudiness, precipitation, wind profiles and visibility, as described by Park and Xu (1999), and the problem with rain gauges studied by Robinson et al (2004)),…”
Section: Observation Biases and Limitationsmentioning
confidence: 99%
“…It is difficult to define a suitable height for the gauge rim where the trees are of irregular height or the topography is uneven. Furthermore, the level of the gauge must also be regularly raised in-line with growth of the trees (Robinson et al, 2004).…”
Section: Special Site Considerationsmentioning
confidence: 99%